Sheikh Mohammad Abdullah's Reflections on Kashmir - Khan, Nyla Ali (Springer International Publishing, 2018)
This book is a compendium of the speeches and interviews of Sheikh Mohammad Abdullah, who reigned as Prime Minister of the State of Jammu and Kashmir from 1948 to 1953, and who was a large presence on the political landscape of India for fifty years. The volume is designed to enable a student of South Asian politics, and the politics of Kashmir in particular, to analyze the ways in which experiences have been constructed historically and have changed overtime.